Apparent or Standardized Ileal Digestibility of Amino Acids of Diets Containing Different Protein Feedstuffs Fed at Two Crude Protein Levels for Growing Pigs - Adebiyi, A. O. (Asian-Australas J Anim Sci, 2015)
The current study determined the apparent or standardized ileal digestibility of amino acids (AID or SID of AA) in growing pigs fed diets containing three protein feedstuffs with different fiber characteristics at two dietary crude protein (CP) levels. Twenty boars (Yorkshire×Landrace) with average initial body weight of 35 (±2.6) kg were fitted with a simple T-cannula at the distal ileum. These pigs were offered six diets containing soybean meal (SBM), canola meal (CM) or corn distillers dried grains with solubles (corn-DDGS) that were either adequate (19%) or marginal (15%) in CP using a triplicated 6×2 Youden Square Design. Except for Met, Trp, Cys, and Pro, AID of AA was greater (p<0.05) in the SBM diet compared with the CM diet. Apparent ileal digestibility for Gly and Asp was greater (p<0.05) in the SBM diet compared with the corn-DDGS diet. The AID of Ile, Leu, Phe, Val, Ala, Tyr, and Asp was greater (p<0.05) in the corn-DDGS diet compared with the CM diet. Standardized ileal digestibility of AA was greater (p<0.05) in the SBM diet compared with the CM diet for all AA except Trp and Pro. The SID of Ile, Leu, Val, Ala, Tyr, and Asp was greater (p<0.05) in the corn-DDGS diet compared with the CM diet. It was concluded that protein feedstuff affects ileal AA digestibility and is closely related to dietary fiber characteristics, and a 4-percentage unit reduction in dietary CP had no effect on ileal AA digestibility in growing pigs.